Synthesis and Characterization of Alginate Encapsulated Zirconium-Based Ferromagnetic Sorbent for Adsorptive Removal of Dyes - Fong Lim, Soh; Yung Weng Lee, Agnes; Seng Kam, Yat; N. David Chua, S (International Journal of Engineering and Technology, 2018)
This paper provides insight on the removal of dyes from water using magnetic separation technique. A new alginate encapsulated zirconium-based encapsulated ferromagnetic sorbent has been synthesized by co-precipitation and electrostatic extrusion techniques. The ferromagnetic sorbent has the alginate as outer polymeric shell and zirconium-based iron oxides as inner ferromagnetic cores. The sorbent has the multi-functional properties as it is can be easily separated using external magnetic force, and effective in adsorptive removal of congo red, methyl violet, and methylene blue dyes. The sorbent was characterized by particle size analyser, Scanning Electron Microscope (SEM), Thermal Gravimetric-Differential Thermal Analyzer (TG-DTA), and Fourier Transform Infrared Spectroscopy (FT-IR).Â  Adsorption assays were performed in batch using methyl violet, methylene blue, and congo red dyes as contaminants. The alginate encapsulated zirconium-based ferromagnetic sorbent was a potential candidate for removal of dyes under a magnetic field as separating agent. The present investigation demonstrates the ferromagnetic sorbent exhibiting good performance to remove the methyl violet, congo red, and methylene blue dyes from aqueous solutions. The adsorption experiments reveal that the adsorption performance is higher for the cationic dye than the anionic dye. The SEM and FT-IR studies show that the interaction characteristics between the dyes and the ferromagnetic sorbent where the surface of the ferromagnetic sorbent became smoother and less porous when the metal-O group (Zr-O and Fe-O) of the ferromagnetic sorbent attaches to the dye.Â Â